Outcomes of traumatic brain injury among pediatric population presenting in emergency room - Dr. Karthick Jayapal; Dr. Hassan Adnan Mansour (Pediatric Review: International Journal of Pediatric Research, 2019)
Background: Traumatic Brain Injury (TBI) is one of the most common cause of Emergency Room (ER) visits in the pediatric age group. Severe TBI can result in impairment of higher cognitive functions and can also limit physiological functions like motor, speech and emotional problems. This study was carried out to evaluate the outcomes of TBI among pediatric patients presenting in ER. Methods: This cross-sectional study was carried out among 175 pediatric patients visiting the emergency room with a diagnosis of traumatic brain injury. Patient with moderate to severe traumatic head injury within 72 hours and those aged 1 - 15 years were included. Glasgow coma scale was used to assess and grade the severity of the TBI. Glasgow Outcome Scale was used to grade the outcomes following TBI. Results: As per the Glasgow Outcome Scale (GOS), majority of the participants were graded with mild disability and good recovery (64%), while 6 patients were graded to be dead and 4.6% of the participants were graded to be in vegetative state. In this study, significant correlation between severity of the TBI and its outcome. Moderate TBI was associated with better outcomes compared to severe TBI. The association was found to be statistically significant (p<0.0001). Conclusion: Considering the impact of specific causes of TBI namely motor vehicle accidents and fall from height, there is a need for implementation of rigorous legislations which can minimize the risk for such accidents involving the pediatric age groups. It is essential to create safe public places, which are not only utility based, but also enable vulnerable age groups access them with minimal risk.